Reimagining Social Mobility in the Platform Economy and Automation-Driven Labor Landscape - Sulaksono, Sulaksono; Hardyansah, Rommy; Darmawan, Didit (Metromedia, 2025)
This study examines how digital labor structures and automation technologies are reshaping the conditions for vertical social mobility, particularly among informal workers and young professionals. Through a qualitative literature-based approach, the research explores how gig platforms, algorithmic labor markets, and technological displacement are transforming traditional trajectories of advancement. The findings reveal that the erosion of stable employment, the rise of opaque performance metrics, and the spread of precarious digital work have significantly weakened conventional pathways to economic elevation. Informal workers face structural barriers intensified by algorithmic governance, while young professionals encounter diminishing returns from educational investment. The promise of flexibility and entrepreneurial independence often masks the persistence of inequality and institutional inertia. The study demonstrates that new determinants of social status—digital reputation, access to technology, and platform fluency—have emerged, but remain unevenly distributed. These dynamics call for a reevaluation of how mobility is conceptualized in the context of digitally mediated capitalism. By synthesizing insights from labor sociology, political economy, and technology studies, this research contributes to a more nuanced understanding of social stratification in the twenty-first century.